THE UTILIZATION RATE OF THE LIBRARY SCIENCE STUDY PROGRAM’S E-JOURNAL "KHIZANAH AL-HIKMAH" DURING COVID-19 PANDEMIC BY THE STUDENTS OF THE LIBRARY SCIENCE DEPARTMENT AT UIN ALAUDDIN MAKASSAR - Abidin, Saenal (Jurnal Diskursus Islam, 2022)
The main problem in this study is how much is the utilization rate of the e-journal of the library science study program "khizanah al-hikmah" during the covid-19 pandemic by students of the library science department at UIN Alauddin Makassar. The main problem is further described into several sub-problems, including: How high is the frequency of use of the e-journal of the Library science study program "Khizanah al-hikmah" by students majoring in library science at UIN Alauddin Makassar and what factors influence and the rate of utilization by students majoring in library science at UIN Alauddin Makassar. In this study, the researcher used a descriptive type of research with a quantitative approach, which is a method that uses data in the form of numeric numbers. In this study, the population was all active students majoring in library science in all classes, namely 620 people. The sample in this study was 32% of the population, while 32% of 620 was 198. So the number of respondents in this study was 198 students. Based on the study results, 68.7% of the students knew about the existence of library science e-journals, and 31.3% did not know about library science e-journals. As for the utilization rate of the khizanah al-hikmah e-journal from a total of 68.7% of students who responded to the end or 145 students of a total of 198 respondents, it shows the data used by students of the Library Science study program was 90.1% or was in very high category. As for the rate of utilization of each indicator, that is a factor of utilization by students; on average, it is in the high category.